Cultural Dimensions of Czech Republic and Argentina, to foster Competitiveness - Farhi-Zimmerman, Mariela (2020)
ABSTRACT My thesis underscores the differences separating Argentine and Czech business cultures and practices, while showing where and how they can be bridged. I used standard U.S. managerial norms as a reference point. The material I reviewed leads me to the conclude that Argentine firms seeking to do business in the Czech Republic, and vice versa, must master the cultural nuances of both countries. I became interested in this subject during the three years I lived in Prague, from 2011-2014. As a resident of the Czech Republic, I came to marvel the system of public transportation upon which the country relies. Trams, trains, and busses are ubiquitous there. Czech systems are efficient, low cost, and undoubtedly one of key reasons the Czech capital both maintains, and has retained, its attractiveness as a tourist destination. My native Argentina once relied heavily on a national rail system, as Czechs still do. In The South American state’s cultural identity resembles its Czech counterpart on this respect. Just as Czechs and the country’s neighbors view with pride the famed Skoda Works, Argentina’s identity was entwined with railways and agriculture. It was British workers who developed the South American state’s railway network, upon which beef and other exports depended. They also played football and formed clubs, giving birth to Argentina’s passion and point of pride, as well as the export of star players to Europe. The neoliberalism doctrine 1990s saw the abandonment of the great Argentine rail system, which fell into disrepair and was sold off or abandoned. Trains, planes, and automobiles never did replace the rails. The economic gap between the capital and its provinces continued to grow; the Argentine economy never really recovered. The fall of communism led to the selling of Czech state enterprises (in Czechoslovakia, the predecessor state at the time). Those similarities end here.